A Simple and Sensitive UPLC–UV Method for Simultaneous Determination of Isoniazid, Pyrazinamide, and Rifampicin in Human Plasma and Its Application in Therapeutic Drug Monitoring - Jiang, Zhimei; Huang, Liang; Zhang, Lingli; Yu, Qin; Lin, Yunzhu; Fei, Haotian; Shen, Hongxin; Huang, Hong (Frontiers in Molecular Biosciences, 2022)
As the first-line anti- tuberculosis (TB) drugs, pyrazinamide (PZA), isoniazid (INH) and rifampicin (RFP) are playing vital roles for curbing rapid spread of TB. Precise quantification of these drugs in biological samples is crucial to evaluate or improve the efficacy of advanced TB drug delivery systems, which are designed for reducing drug resistance, minimizing side effects etc. Herein, a simple and sensitive method based on UPLC-UV was developed and validated for simultaneous determination of PZA, INH and RFP in human plasma, and was applied to anti-TB drug therapeutic drug monitoring. The analytes were implemented on an HSS T3 C18 column at 40 °C. The separation was performed with a gradient elution begin with methanol-acetonitrile-water (3:3:94) at 0.1 mL/min. Analysis required 100 µL of plasma and involved a rapid and simple protein precipitation with methanol-acetonitrile (1:1). The results demonstrated that the calibration curves were linear in range of 0.5~20 µg/mL, 5~60 µg/mL and 5~60 µg/mL for INH, PZA and RFP, respectively. The precision of intra- and inter-day was less than 15%, and the LLOQ was identifiable and reproducible at 0.5 µg/mL for INH, 5 µg/mL for PZA and RFP, respectively. The analytes in plasma were stable after being stored for 21 days at -80 °C. Our results indicated that this method is applicable to the simultaneous monitoring of INH, PZA and RFP in human plasma.